A PERSPECTIVE STUDY ON AQUA CULTURE’S PROBLEMS AMONG COASTAL ANDHRA - Raju, M L N (IJRDO - Journal of Applied Management Science, 2016)
Aquaculture has been a fast-growing industry because of significant increases indemand for fish and seafood throughout the world. Aquaculture plays a significant role in thedevelopment of the country economy as well as state economy Coastal environment hasundergone rapid change in recent times. Change in the state of the environment ismultifaceted, but a key concern is the way that natural habitats the coastal zone ischaracterized by ambiguities of resource ownership and a complex web of interactions amongpeople, resources and ecosystems. Conflicts exist between the needs of people who may gainfrom intensification of land use for agriculture and or aquaculture and other people who areLivelihoods may be adversely affected by environmental impacts. Mainly Fish were exposed toany toxicant of different concentrations, due to stress the physiology gets disturbed, thusconsiderably affects so in this research paper represent the facing various environmentalProblems and approaches to managing change in the inland coastal zone in Andhra Pradesh.